2022
DOI: 10.2147/ptt.s328572
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity in Adult Psoriasis: Considerations for the Clinician

Abstract: Psoriasis is associated with several comorbidities ranging from cardiovascular comorbidity and mental disorders to other immune mediated inflammatory diseases. However, most of these co-morbidities are often overlooked or diagnosed late. Furthermore, evidence suggests that comorbidities are undertreated. Here, we provide an overview of comorbidities in psoriasis and present a simple rundown of considerations of relevance to the clinician. We hope that this review may raise clinicians’ awareness of comorbiditie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 163 publications
(144 reference statements)
0
6
0
Order By: Relevance
“…Psoriasis is commonly associated with mental disorders, especially depression and anxiety [ 7 ]. Psoriasis is a lifelong relapsing-remitting illness that negatively impacts people's quality of life (QoL).…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Psoriasis is commonly associated with mental disorders, especially depression and anxiety [ 7 ]. Psoriasis is a lifelong relapsing-remitting illness that negatively impacts people's quality of life (QoL).…”
Section: Reviewmentioning
confidence: 99%
“…The global burden of disease study found that 5.6 million persons of all age groups had disability-adjusted life years (DALYs) related to psoriasis in 2016 [ 4 ]. Another term for psoriasis is "systemic disease having multiple comorbidities,” i.e., cardiovascular disease (CVD), psoriatic arthritis (PSA), and mental disorders [ 7 ]. Psoriasis is the most common chronic skin disorder, negatively affecting psychological interactions and health.…”
Section: Introductionmentioning
confidence: 99%
“…The clinical characteristics of psoriasis include silvery scales, red plaques, and skin thickening. Psoriasis has been associated with several comorbidities, including cardiovascular disorders, depression, social isolation, and all-cause mortality (Daugaard et al, 2022). Patients with psoriasis also have an increased risk of melanoma and non-melanoma skin cancers (Coates et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Psoriasis may cause social stigmatization and degrade the patients’ quality of life 3 , 4 . Recently, multiple studies have reported that psoriasis 1 is associated with not only previously well-known comorbidities—such as psoriatic arthritis, Crohn's disease, and uveitis—but also other chronic diseases, including cardiovascular disease, hypertension, diabetes, hyperlipidemia, and even psychiatric comorbidities 5 7 . Therefore, psoriasis is considered a systemic disease with a fairly high burden.…”
Section: Introductionmentioning
confidence: 99%